Mediating Effect of Organizational Support in the Effect of Perceived Justice, Empowerment and Employees` Adaptability on Organizational Commitment - Mehdi Yazdanshenas; Yaser Ghanei (مطالعات منابع انسانی, 2020)
Background & Purpose:Organizational commitment as one of the most important job attitudes has always been considered by researchers and scholars. This research was conducted to investigate the effects of empowerment, perceived justice, and employees` adaptability on organizational commitment in which the role of organizational support has also been considered. Methodology:This research is an applied and descriptive research that has been done by survey method. The statistical population of the study was all employees of District 6 of Tehran Municipality from which a random sample was selected. The required data were collected through a questionnaire and analyzed using structural equation modeling. Findings:Data analysis showed that psychological empowerment, employees' perception of justice and employee adaptability directly affect organizational commitment. In addition, these variables indirectly affect organizational commitment through perceived organizational support.   Conclusion:According to the model presented in this study, focusing on employees` psychological empowerment, perceived justice and adaptability of employees can improve perceived organizational support and employees` organizational commitment. Organizational Support, Perceived Justice, Empowerment, Employees` Adaptability, Organizational Commitment.